Spectral Properties of Marennine-like Pigments Reveal Minor Differences Between Blue Haslea Species and Strains - Amina Latigui; Boris Jacquette; Jens Dittmer; Jean-François Bardeau; Edouard Boivin; Lucie Beaulieu; Pamela Pasetto; Jean-Luc Mouget (Molecules)
Marennine is the specific bluish pigment produced by the marine diatom Haslea ostrearia Gaillon (Simonsen), responsible for the greening of oysters in France’s Atlantic coast. For decades, H. ostrearia was considered the only blue diatom and described as such. However, new blue Haslea species have been described recently, among which Haslea karadagensis Davidovich, Gastineau, and Mouget (Black Sea, Crimea, Ukraine); Haslea provincialis Gastineau, Hansen, and Mouget (Mediterranean Sea, southern France); Haslea silbo Gastineau, Hansen, and Mouget (West Atlantic Ocean, USA); and one not characterized yet, Haslea sp. nov., isolated in Tenerife (Spain). These species produce marennine-like pigments, for which little information is available yet. The present work aims at studying spectral characteristics of these pigments by UV–visible spectrometry, Raman spectrometry, infrared spectrometry, nuclear magnetic resonance, energy-dispersive X-ray spectroscopy, and cyclic voltammetry, and comparing them to those of marennine produced by H. ostrearia strains originating from the north Atlantic Ocean (western France and Macaronesia), and north Pacific Ocean (southwestern USA). Results show that marennine produced by H. ostrearia strains and marennine-like pigments produced by H. provincialis, H. silbo, and Haslea sp. nov. are quite similar regarding their polysaccharide skeleton, and absorption in the UV–visible, infrared, and Raman regions. The most different marennine-like pigment is produced by H. karadagensis, but all Haslea blue pigments studied so far belong to the same family of organic molecules.